1996
DOI: 10.1104/pp.112.1.401
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Abscission Induced by Ethylene in Water-Stressed Intact Seedlings of Cleopatra Mandarin Requires Previous Abscisic Acid Accumulation in Roots

Abstract: The involvement of abscisic acid (ABA) in the process of leaf abscission induced by 1 -aminocyclopropane-1 -carboxylic acid (ACC) transported from roots to shoots i n Cleopatra mandarin (Citrus reshni Hort. ex Tan.) seedlings grown under water stress was studied using norflurazon (NF). Water stress induced both ABA (24-fold) and ACC (16-fold) accumulation in roots and arrested xylem flow. Leaf bulk ABA also increased (&fold), although leaf abscission did not occur. Shortly after rehydration, root ABA and ACC r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
144
1
28

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(188 citation statements)
references
References 9 publications
15
144
1
28
Order By: Relevance
“…Different authors have associated the decrease in FW or DW with a reduction in the number of leaves or in leaf abscissions (Table 1). To offer an explanation, some experiments have shown that a specific Cl − build-up in the leaves of salt-stressed plants triggers 1-aminocyclopropane-1-carboxilic acid (ACC) synthesis and its conversion to ethylene with high efficiency, releasing enough hormone to trigger leaf abscission as occurred in citrus leaves and other plants [58][59][60][61]. Salt and osmotic stress also promoted the conversion of ACC to ethylene in the halophyte Allenrolfea occidentalis [62].…”
Section: Introductionmentioning
confidence: 99%
“…Different authors have associated the decrease in FW or DW with a reduction in the number of leaves or in leaf abscissions (Table 1). To offer an explanation, some experiments have shown that a specific Cl − build-up in the leaves of salt-stressed plants triggers 1-aminocyclopropane-1-carboxilic acid (ACC) synthesis and its conversion to ethylene with high efficiency, releasing enough hormone to trigger leaf abscission as occurred in citrus leaves and other plants [58][59][60][61]. Salt and osmotic stress also promoted the conversion of ACC to ethylene in the halophyte Allenrolfea occidentalis [62].…”
Section: Introductionmentioning
confidence: 99%
“…This abscission may be due to hormonal imbalance and enhanced synthesis of the endogenous plant hormones ethylene (Gomez-Cadenas et al, 1996). In water stress conditions (50% and 25% FC) 'Rabab' cultivar had higher RWC than 'Shi Medrano shehgap'.…”
Section: Discussionmentioning
confidence: 99%
“…However, other research lines showed that stomatal closure occurs independently of the increase in xylem ABA concentration Dodd et al, 2008b;Puertolas et al, 2014;Carvalho et al, 2016). Additionally, further evidence contrasted with the original model such as the ability of leaves to synthetize by themselves large amounts of ABA (Gómez-Cadenas et al, 1996;Holbrook et al, 2002;Christmann et al, 2005) or the low ability of roots to accumulate carotenoids, the ABA direct precursors (Parry and Horgan, 1992;Ruiz-Sola et al, 2014;.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, investigations should consider the longer distance existing between green tissues and roots in woody plants and not only the structural and anatomical differences (Popko et al 2010). To this respect, Citrus has been successfully used as a tree model for studying plant responses to environmental stress (de Ollas et al 2013, Gómez-Cadenas et al 1996, Pérez-Clemente et al 2012). …”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation